Non-digital adaptive assessment in early literacy contexts: A document analysis of pre-service elementary teacher internship reports (Diniyah: Jurnal Pendidikan Dasar, 2026)
Written test-based assessment often fails to accurately represent early-grade students’ understanding when their literacy skills are still developing. This study aims to analyze non-digital adaptive assessment practices in early literacy contexts and formulate a more inclusive conceptual assessment model. A qualitative document analysis design was employed by examining ten internship reports written by pre-service elementary teachers in Manggarai, Indonesia. The data were analyzed using thematic analysis to identify patterns of assessment practices, pedagogical rationales, and learning implications. The findings show that adaptive assessment was enacted through oral questioning, observation of learning processes, hands-on performance assessment, and contextual tasks grounded in students’ everyday experiences. These strategies reduced dependence on reading and writing as the sole medium of assessment while enabling students to demonstrate understanding in more authentic ways. The study confirms that adaptive assessment does not necessarily require digital technology but can be developed through teachers’ pedagogical flexibility. These findings imply the need to strengthen assessment equity, inclusive learning, and evaluative validity in early-grade elementary classrooms. Keywords: authentic assessment; document analysis; early literacy; elementary education; internship reports; non-digital adaptive assessment